MCKIP Delegation First Visit to UMP Pekan - Yong, Ying Mei (2018)
Pekan, 27 September - The MCKIP-based Alliance Steel Sdn. Bhd. visited Universiti Malaysia Pahang (UMP) Pekan campus for the first time last Thursday. Alliance Steel (M) Sdn. Bhd. has been operating at the Malaysia-China Kuantan Industry Park (MCKIP), Gebeng, Kuantan, Pahang since 2014.